2018
DOI: 10.1007/s00436-018-5907-6
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of Taenia pisiformis metacestodes and high sex-associated susceptibility to cysticercosis in naturally infected wild rabbits

Abstract: Sexual dimorphism is a well-documented phenomenon observed at all levels of the animal kingdom, with the inclusion of both sexes in clinical trials and basic research becoming mandatory. Regarding parasitosis, in several animal species, the signs and virulence of the disease may change depending on the sex of the affected animal. In the cestodiasis caused by Taenia solium and Taenia crassiceps, females are more susceptible to experimental infection than males. Cysticercosis by Taenia pisiformis in rabbits has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…This observation was attributed to a decrease in chemical mediators such as IFN-α and IFN-β, as well as a reduction in the cytotoxic capacity of NK cells [ 19 ]. This finding is consistent with our observation in the obese-infected rabbits, in which the total number of metacestodes was higher and all animals were infected; it is important to note that T. pisiformis is a parasite that naturally infects wild and domestic rabbits and hares [ 2 , 20 ]. Therefore, it is of interest to study the mechanisms associated with the susceptibility to infection observed in obese rabbits, especially the role of cytokines in this comorbidity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation was attributed to a decrease in chemical mediators such as IFN-α and IFN-β, as well as a reduction in the cytotoxic capacity of NK cells [ 19 ]. This finding is consistent with our observation in the obese-infected rabbits, in which the total number of metacestodes was higher and all animals were infected; it is important to note that T. pisiformis is a parasite that naturally infects wild and domestic rabbits and hares [ 2 , 20 ]. Therefore, it is of interest to study the mechanisms associated with the susceptibility to infection observed in obese rabbits, especially the role of cytokines in this comorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…Parasitic diseases affect a third of the world population; both humans and animals are parasitized at some stage of their lives [ 1 ]. The metacestode of Taenia pisiformis ( T. pisiformis ) is a very frequent parasite in farm rabbits and in pets, being very frequently found in lactating and pregnant wild does [ 2 ]. It has been documented that infection in rabbits reduces litter size by 50%, with an increase in serum progesterone levels [ 3 ]; the adult stage of T. pisiformis causes behavior modifications in experimentally infected hamsters [ 4 ] and the metacestode in domestic rabbits [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our work, three species of Taenia were identified using molecular techniques: T. pisiformis , T. serialis , and T. hydatigena . The first two were found in the east area of the Mexicali valley where grains and forages are the dominant agricultural crops, with an abundance of lagomorphs such as rabbits and other rodents associated with the biological cycle of T. serialis and T. pisiformis [ 20 , 21 ]. Dog gets infected while hunting and consumes the intermediate host, acquiring the metacestodes and completing the biological cycle of these parasites [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oryctolagus cuniculus become infected through ingestion of water or forage contaminated with T. pisiformis eggs. Cysticerci usually parasitize the liver capsule, peritoneum, greater omentum and mesentery, and occasionally other organs such as the pelvis or lungs [3,4]. Rabbits infected with T. pisiformis have a weakened immunologic resistance and are susceptible to secondary infections with other pathogens, which may cause host digestive disorders, growth retardation, a decrease in feed conversion, reduction of proliferation, and even death [5].…”
Section: Introductionmentioning
confidence: 99%